Worries of Pregnant Women: Testing the Farsi Cambridge Worry Scale - Forough Mortazavi (Scientifica, 2016)
Pregnancy adds many sources of concerns to women’s daily life worries. Excessive worry can affect maternal physiological and psychological state that influences the pregnancy outcomes. The aim of this study was to validate the Cambridge Worry Scale (CWS) in a sample of Iranian pregnant women. After translation of the CWS, ten experts evaluated the items and added six items to the 17-item scale. In a descriptive cross-sectional study, 405 of pregnant women booked for prenatal care completed the Farsi CWS. We split the sample randomly. Exploratory factor analysis (EFA) was conducted on the first half of the sample to disclose the factorial structure of the 23-item scale. The results of the EFA on the Farsi CWS indicated four factors altogether explained 51.5% of variances. Confirmatory factor analysis (CFA) was done on the second half of the sample. The results of the CFA showed that the model fit our data (chi-square/df = 2.02, RMSEA = 0.071, SRMR = 0.071, CFI = 0.95, and NNFI = 0.94). Cronbach’s alpha coefficient for the Farsi CWS was 0.883. The Farsi CWS is a reliable and valid instrument for understanding common pregnancy worries in the third trimester of pregnancy in Iranian women.